The adventures of Tom Sawyer : Mark Twain. - SparkNotes LLC.; Twain, Mark, 1835-1910. (London : George g. Harrap & Company LTD)
SparkNotes Literature Guides: Making the reading experience fun! When a paper is due, and dreaded exams loom, here's the lit-crit help students need to succeed! SparkNotes Literature Guides make studying smarter, better, and faster. They provide chapter-by-chapter analysis; explanations of key themes, motifs, and symbols; a review quiz; and essay topics. Lively and accessible, SparkNotes is perfect for late-night studying and paper writing. Includes: An A+ Essay--an actual literary essay written about the Spark-ed book--to show students how a paper should be written. 16 pages devoted to writing a literary essay including: a glossary of literary terms Step-by-step tutoring on how to write a literary essay A feature on how not to plagiarize.
P.B
P.B
Includes bibliographical references.
Keywords: Sawyer, Tom -- (Fictitious character); Twain, Mark, -- 1835-1910 -- Criticism and interpretation; Twain, Mark, -- 1835-1910. -- Examinations -- Study guides; Sawyer, Tom -- (Fictitious character); Twain, Mark, -- 1835-1910.; Adventures of Tom Sawyer (Twain, Mark); Examinations; STUDY AIDS -- Book Notes (see also JUVENILE NONFICTION -- Study Aids -- Book Notes); Electronic books; Criticism, interpretation, etc; Study guides